Selling through tough times : grow your profits and mental resilience through any downturn - Reilly, Paul (Sales training consultant) ([McGraw Hill], 2021)
"A timely and indispensable guide to thriving in a challenging sales environment-while hanging on to profits As a salesperson and sales manager, you know that it's harder to sell in tough times-whether it's a global pandemic, recession, or industry-wide challenge. But somehow there are always successful "tough-timers" that not only survive, but thrive through tough times. What do they have-and what do they know-that keeps them on top? In Selling Through Tough Times, Paul Reilly lays it out in clear and straightforward terms: Customers buy differently in tough times, so salespeople need to sell differently in tough times. In this timely and indispensable guide, you'll discover how to develop the right mindset and adapt your skills to prevail in a challenging climate. Reilly's plan includes immediate action items (including six Daily Mental Flex activities) to longer-range strategies. The principles of selling are constant, but tactics change in tough times. Reilly's tactical plan includes redefining value in customer terms, repositioning products and services for tough times, and different persuasion tactics. You'll learn how to select and pursue the right opportunities, discover needs, persuade effectively, win more deals, and-crucially-protect profit, by embracing the "tough-timers" mental attitude and executing the critical selling activities"--